Association between epicardial adipose tissue and coronary artery vasospasm during pulmonary vein isolation. Issue 2 (9th March 2018) - Minami, Kentaro; Kumagai, Koji; Sugai, Yoshinao; Nakamura, Kohki; Naito, Shigeto; Oshima, Shigeru
Abstract: Coronary artery vasospasms (CAVs) during pulmonary vein isolation have been reported, but the mechanism remains unclear. We experienced a rare case of CAVs caused by radiofrequency (RF) applications to sites with massive epicardial adipose tissue (EAT) attached. Because EAT contains ganglionated plexuses, RF application may have caused an autonomic nervous system imbalance, which thereby provoked severe CAVs.